The Role of Simile in Depicting The Unseen in Prophetic HadithsExamples from Sahih Al Bukhari (Damascus University Journal of arts and humanities sciences, 2025)
The Prophetic discourse is distinguished by its characteristics that place it in a superior position among all educational and aesthetic discourses, with its immense ability to clarify and influence through the use of linguistic and rhetorical devices.The use of simile was the most prominent rhetorical art in the Prophetic tradition in bringing the hidden and mysterious to the tangible and comprehensible, especially in communicating the unseen matters that the Prophet was informed of and instructed to convey. This study sought to highlight the Prophet's use of simile in depicting the unseen matters by examining authentic Hadiths from Sahih Al-Bukhari and studying the Hadiths related to the unseen matters, whether past, present, or future. It emphasizedthe importance of bringing meaning closer to the recipient's mind, influencing them, and stimulating their imagination through the use of simile. The study employed a descriptive-analytical approach in the analysis of the Hadiths on unseen matters.The research included an introduction defining simile, highlighting its importance and main functions, and three chapters. The first chapter explained the effectiveness of simile in depicting the unseen matters, the second chapter discussed the use of the elements of simile in depicting the unseen matters, and the third chapter mentioned the purposes of simile in portraying the unseen matters. Finally, the conclusion highlighted the key findings and recommendations.
Keywords: Simile; Depiction; Unseen Matters; Prophetic; Clarification; Influence